2006
DOI: 10.1002/bdra.20340
|View full text |Cite
|
Sign up to set email alerts
|

Adult index patient with Currarino syndrome due to a novel HLXB9 mutation, c.336dupG (p.P113fsX224), presenting with Hirschsprung's disease, cephalgia, and lumbodynia

Abstract: Molecular diagnostics may be helpful in cases of Hirschsprung's disease accompanied by other symptoms suggestive for Currarino syndrome, since it can lead to major complications such as perianal sepsis, meningitis, and malignant transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
0
9
0
3
Order By: Relevance
“…They are scattered along the coding sequence, although the largest proportion is localized to the first exon, with a hotspot within a six cytosine and a six guanine repeat located between nucleotides 48_54 and 331_336: four cases were observed in our series, Hagan et al [2000] reported three cases, Kochling et al [2001] two cases, and Volk et al [2007] one case.…”
Section: Cytogenetic Anomaliesmentioning
confidence: 57%
See 2 more Smart Citations
“…They are scattered along the coding sequence, although the largest proportion is localized to the first exon, with a hotspot within a six cytosine and a six guanine repeat located between nucleotides 48_54 and 331_336: four cases were observed in our series, Hagan et al [2000] reported three cases, Kochling et al [2001] two cases, and Volk et al [2007] one case.…”
Section: Cytogenetic Anomaliesmentioning
confidence: 57%
“…Series of patients reporting clinical data and molecular studies followed with a mutation detection rate of about 50% overall and up to 90% in familial cases [Ross et al, 1998;Belloni et al, 2000;Hagan et al, 2000;Kochling et al, 2001;Martucciello et al, 2004;Urioste et al, 2004;Garcia-Barcelo et al, 2006;Wang et al, 2006;Liang et al, 2007;Volk et al, 2007]. A broad inter-and intrafamilial phenotypic variability is observed [Ross et al, 1998;Belloni et al, 2000;Hagan et al, 2000;Kochling et al, 2001] that accounts for late-onset CS or even undiagnosed cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baltogiannis et al [30], Volk et al [31], Martucciello et al [21] ont rapporté 4 cas de SC associés à une maladie de Hirschsprung. Dans une étude récente de 6 cas de SC, Martucciello rapporte également un cas de dysganglionose non étiquetée [21].…”
Section: Masse Pré-sacréeunclassified
“…We, therefore, hypothesized that genes responsible for non-syndromic HSCR were promising candidate genes in the present family, and we sequenced the major HSCR genes (RET, EDNRB, EDN3, and GDNF) in our index patient. Since six patients with Currarino syndrome, which includes ARM as a main feature, and associated Hirschsprung's disease [2,3,20,25,43] have been reported, we also screened for HLXB9 mutations. Moreover, we aimed to identify microaberrations characterized by loss or gain of genomic material that might contribute to ARM in this family at a genome-wide level.…”
Section: Introductionmentioning
confidence: 99%